PENERAPAN FUZZY TAHANI PADA REKOMENDASI OBJEK WISATA DI JAKARTA - Veronika; Dedi Trisnawarman (Fakultas Teknologi Informasi Universitas Tarumanagara, 2023)
Tourism is an important sector in building the Indonesian economy. Jakarta as the nation's capital has a variety of tourist destinations that can be an attraction for tourists to visit the city. Due to diverse destinations, tourists find it difficult to choose destinations to visit according their preferences. Therefore, a decision support system is needed in recommending tourist destinations in terms of the average 3 stars hotel price, the number of nearby restaurants, the distance from airport to tourism and destinations rating. This study aims to develop a decision support system based on Fuzzy Tahani in recommending Jakarta tourist destinations. The decision support system development method uses the stages of Rapid Application Development,, which consist of requirement analysis, design, implementation and testing. The results of this study are designing a decision support system that applies the Fuzzy Tahani algorithm method with an interface in the form of a web page that helps tourists get recommendations based on the criteria entered. For the testing there are two tests, fuzzy algorithm testing by comparing fuzzy algorithm calculations manually with calculations from the system and Black Box testing to test the suitability of the functionality of the decision support system.